The effect of mosses on the relocation of SOC and total N due to soil erosion and percolation in a disturbed temperate forest - Gall, Corinna; Nebel, Martin; Scholten, Thomas; Seitz, Steffen (Frontiers in Forests and Global Change, 2024)
Forests cover one-third of the global land and are important components of carbon and nitrogen cycling. Anthropogenic disturbances, such as forest road systems or skid trails for timber harvesting, can dramatically change the nutrient cycling in these ecosystems. Skid trails increase soil erosion and thus the displacement of soil organic carbon (SOC) and total nitrogen (Nt). Additionally, runoff transports high amounts of dissolved organic carbon (DOC), which can have a negative impact on aquatic ecosystems. One of the most important countermeasures against soil erosion is the quick recolonization of vegetation. To date, the extent to which natural vegetation succession influences the relocation of SOC and Nt, and in particular the role of mosses in this context, has not been well investigated. This study investigates the influence of natural vegetation succession and in particular of mosses on the displacement process of SOC and Nt as well as DOC caused by soil erosion. To this end, we combine the results of a field study using in-situ rainfall simulations with small-scale runoff plots in skid trails of the Schönbuch Nature Park in south-western Germany with the results of ex-situ rainfall simulation experiments with infiltration boxes containing the substrate from the respective skid trails. The eroded sediments of skid trails were on average enriched in SOC by 16% and in Nt by 35% compared to the original soil, which lead to a decrease of the C/N ratio in sediments. As vegetation succession progressed, the displacement of SOC and Nt was reduced, confirmed by a negative correlation between the enrichment ratios of SOC (ERSOC), Nt and total vegetation cover. However, mosses tended to reduce ERSOC more than vascular plants. Additionally, mosses significantly decreased DOC concentration in surface runoff compared to bare soils, while no difference in DOC concentration in percolated water could be observed. Future research should explore the role of mosses in the storage of SOC and Nt in the soil and their impact on soil stability. Thus, utilizing mosses could potentially minimize environmental impacts from soil disturbances in forests.